Immune function analysis of LsSd, a transcription factor of the Hippo signaling pathway, in the cigarette beetle Lasioderma serricorne - Zhang, Yue; Yang, Jiapeng; Dai, Renhuai; Yang, Wenjia; Zhang, Xiaomin (Frontiers in Physiology, 2022)
The Scalloped (Sd) is a transcription factor that regulates organ size control in the Hippo-signaling pathway. Recent studies have showed that Hippo signaling also functions in the innate immune response. Although the Sd gene has been reported in many insects, their immune functions remain unexplored. In this study, the LsSd gene of Lasioderma serricorne, with a complete open reading frame that encodes a protein composed of 402 amino acids was identified. LsSd was predominantly expressed in early pupae. Tissue-specific analyses revealed that the highest concentrations of LsSd were detected in the midgut and brain. At 1 to 24 h after Escherichia coli infection, LsSd expression increased substantially. However, LsSd expression was downregulated 3–12 h after Staphylococcus aureus infection. RNA interference-mediated silencing of the LsSd transcript resulted in deformed, considerably smaller, and degenerated wings. Meanwhile, LsCycE, LsDiap1, and LsVg, which are involved in cell proliferation and wing development, were drastically reduced when LsSd was depleted. In a survival assay, the LsSd knockdown considerably decreased the susceptibility to S. aureus, a gram-positive bacterium. In addition, knockdown of LsSd remarkably downregulated the transcription of LsCact in response to S. aureus stimulation, while upregulating the expression of five immune-related genes. Our results provide conclusive proof for the important roles of LsSd in the immune response of L. serricorne.